Writing-Unwriting: Paradoxes of Ending in Contemporary EnglishLanguage Metafiction Mark Z. Danielowski Alasdair Gray, Lance Olsen Will Self - Raneen Muwafaq Fadhil (Genius Journals, 2025)
This research will focus on the ideas of finitude and finality relating to the production of a literary discourse informed by writing as unwriting It will highlight the different forms of erasure, an act itself producing meaning, of which the text, language and speech, in other words the logos are the object in a formal or metaphorical manner in the works of the corpus , finally we will see that these phenomena of disappearance, dilution or even suppression are all metafictional and/or metatextual manifestations of an aesthetic finality ,By sabotaging the textuality of their metafictions, the authors under study desacralize the text and establish games of connivance with the reader, sometimes pushing him into his entrenchments during the process of receiving the work: we return to the concept of ergodic literature mentioned above , the novels in the corpus illustrate phenomena of linguistic creation and destruction that translate, on the one hand, the perception of a contemporary world devoid of any referential stability and on the other, the desire for a reinvention of authorial speech and literature
Keywords: entrenchments; textuality; suppression